Understorey removal effects on tree regeneration in temperate forests: A meta‐analysis. Issue 1 (23rd November 2020) - De Lombaerde, Emiel; Baeten, Lander; Verheyen, Kris; Perring, Michael P.; Ma, Shiyu; Landuyt, Dries
Abstract: The unwanted development of dense understorey vegetation composed of resource‐acquisitive, tall plant species competing strongly with tree regeneration can pose formidable problems for managers attempting to regenerate temperate forests. Despite many studies on the effects of understorey removal, no comprehensive review has summarised and quantified its effects on subsequent life stages of tree regeneration in temperate forests. We synthesised data from 32 experimental studies from temperate forest regions. We used meta‐analytic techniques to find general patterns in terms of the characteristics of the understorey, overstorey and characteristics of the regenerating tree species, which are most responsible for possible positive understorey removal effects on early life stages of tree regeneration, i.e. emergence, survival and growth. Both seedling survival and growth increased in response to understorey removal; emergence did not show a clear pattern. Seedlings growing free from competition mainly increased their biomass growth (total and above‐ground), whereas diameter and height growth responded less. These positive effects were largest when removing denser understorey vegetation and under more open overstorey conditions. Multiple management options influenced the regeneration responses to understorey removal. For instance, growth of older, planted seedlings responded less to removal, whereas protection against large browsers increased growth responses. Tree species with differing strategies responded differently to understorey removal. Growth and survival responses of early‐successional species responded more strongly to understorey removal than mid‐ or late‐successional tree species. Synthesis and applications . Our study showed that understorey removal can have strong positive effects on tree regeneration across temperate forest contexts. The magnitude of these effects depended on overstorey and understorey conditions, but also on the type of tree species that is regenerated. Our results can support forest managers in their decision‐making and help assess under what conditions understorey removal will be most justified. Abstract : Our study showed that understorey removal can have strong positive effects on tree regeneration across temperate forest contexts. The magnitude of these effects depended on overstorey and understorey conditions, but also on the type of tree species that is regenerated. Our results can support forest managers in their decision‐making and help assess under what conditions understorey removal will be most justified.